A Code of Conduct Is Imperative for Ocean Carbon Dioxide Removal Research - Loomis, Rebecca; Cooley, Sarah R.; Collins, James R.; Engler, Simon; Suatoni, Lisa (Frontiers in Marine Science, 2022)
As the impacts of rising temperatures mount and the global transition to clean energy advances only gradually, scientists and policymakers are looking towards carbon dioxide removal (CDR) methods to prevent the worst impacts of climate change. Attention has increasingly focused on ocean CDR techniques, which enhance or restore marine systems to sequester carbon. Ocean CDR research presents the risk of uncertain impacts to human and environmental welfare, yet there are no domestic regulations aimed at ensuring the safety and efficacy of this research. A code of conduct that establishes principles of responsible research, fairness, and equity is needed in this field. This article presents fifteen key components of an ocean CDR research code of conduct.